PP RI No.18 Th.2000 ttg perubahan ketiga atas PP No.17 Th.99 ttg Badan penyehatan perbankan nasional ... - [Tidak Terdaftar] (Panca Usaha, 2000)
PP RI No.18 Th.2000 ttg perubahan ketiga atas PP No.17 Th.99 ttg BPPN